REMOVAL OF IMPULSE BURSTS IN SATELLITE IMAGES - Tsymbal, Oleg; Lukin, Volodymyr; Koivisto, Pertti; Melnik, Volodymyr (International Journal of Computing, 2014)
Characteristics of impulse bursts in satellite images are analyzed and methods for burst removal are consid- ered. Artificial compact burst model is proposed and test images are created. An advanced multipass algorithm for the detection and removal of compact bursts in the presence of both additive and multiplicative noise is proposed. The efficiency of the algorithm is evaluated quantitatively using the artificial test images and visually using the artificial test images and real radar and optical satellite images. It is shown through experiments that the proposed method removes impulse bursts efficiently while preserving information.